Elevated Serum Vitamin B12 Levels as a Prognostic Factor for Survival Time in Metastatic Cancer Patients: A Retrospective Study. (2nd January 2018) - Oh, Hye Kyung; Lee, Jee Young; Eo, Wan Kyu; Yoon, Seong Woo; Han, Sung Nim
ABSTRACT: Background : Serum vitamin B12 levels have been proposed as one of the survival prediction factors, although no survival analysis in metastatic cancer patients has been conducted yet. This study examined whether serum vitamin B12 levels could be a prognostic factor in metastatic cancer patients. Methods : Data from a retrospective chart review were used to perform Kaplan-Meier and multivariate analyses of the Cox proportional hazards. Subgroup analysis was performed on patients without a liver lesion (hepatocellular carcinoma or liver metastasis). Results : A total of 523 patients were included. The median survival time was 1.8 months (mo) in the high B12 group (>911 pg/mL) and 5.1 mo in the normal B12 group (211–911 pg/mL) ( p < 0.001). In patients without a liver lesion, the median survival times were 2.1 and 6.1 mo in the high and normal B12 groups, respectively ( p < 0.001). Multivariate analysis revealed that serum vitamin B12 level was an independent prognostic factor for overall survival (hazard ratio [HR]: 1.62; 95% confidence interval [CI]: 1.34–1.96, p < 0.001). Conclusion : Serum vitamin B12 level can be used to predict survival time in metastatic cancer patients. Further large-scale cohort studies are required to confirm these findings.